Nutrient Deficiency Analysis on Maize Plant Morphology - Sumiati, Sumiati; Aisyah Chofifawati; Al Faroqi, Nisa Amaliyah Rohmah (Jurnal Biologi Tropis, 2024)
One of the factors that support plants to grow and develop optimally is the availability of sufficient and balanced nutrients and minerals. Providing nutrients that are unbalanced or not in accordance with plant needs will cause symptoms of nutrient deficiencies or nutrient deficiencies. The aims of this research are (1) To determine the symptoms of the morphological appearance of corn plants in the nutrient deficiency treatment, (2) To determine the most dominant morphological appearance of the corn plants in the nutrient deficiency treatment. The type of research used was an experiment using a randomized block design with three replications. The treatment given is the provision of nutrient solutions: complete, -Ca, -S, -Mg, -K, -N, -P, Fe, - Micronutrients and water. The planting media used are cocopeat, roasted husks and a simple hydroponic method (nutrient solution as a planting medium). The parameters observed were plant height, number of leaves, leaf length and leaf width. The results of early indication of nutrient deficiency can be clearly observed in the color of the plant leaves. Leaf chlorosis is a symptom of nutrient deficiency in plants characterized by leaves that are initially green then changes color to yellow or pale. Changes in leaf color are caused by damage or malfunction of chlorophyll.